BUMIPUTERA TEACHERS IN ETHICAL POLITICS - marzius Insani; Ali Imron; Henry Susanto; Wahyuni Atika (FKIP UNIVERSITAS LAMPUNG, 2021)
This study aims to analyze the procurement of Bumiputera teachers to fulfill educational programs in the era of ethical politics. This study uses the historical method, which is the process of testing and analyzing events in the past. The results of this study indicate that the Dutch East Indies government made various efforts to overcome the shortage of teachers by building special teacher education schools such as the Apprenticeship System, CVO (Cursus Volks Onderwijzer), 2-year Normalcursus, Normalschool, Kweekschool, Hongere Kweekschool, Hollands Inlandse Kweekschool, Hoofdacte Course. The government is also trying to conduct training for bumiputera teachers who are guided by two Dutch teachers to receive Dutch language diplomat education for 2 years. Keyword: Bumiputera Teachers, Education, Ethical Politics, Teacher's School